Intellectual character of metacognition in thinking strategies - Machfauzia, Ayu Niza; Djohan, Dr; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: Metacognition is one aspect of intellectual character about a concept that has been used to refer to a variety of epistemological processes. Metacognition essentially means cognition about cognition; that is, it refers to second-order cognitions: thoughts about thoughts, knowledge about knowledge or reflections about actions. Previous research explained that metacognition is useful in many educational settings and can be transferred from the music classroom to other subject areas. Aims and Objective: This study aims to reveal aspects of student metacognition as a strategy used in playing music. Materials and Methods: In this observational study, the spontaneous metacognitive behavior of students during guitar lessons in guitar classroom was analyzed. Results: Data from interviews revealed that students were weak in metacognitive behavior, so that students do not use thinking ways of thinking. This is because the lecturer cannot promote metacognition by designing and implementing instructional strategies that encourage music students to engage in reflection, self-assessment, and thinking critically.Based on the results of research that has been obtained, it can be said that in playing music, especially in the guitar class, it is important to know what is known about the music that will be played. Conclusion: Lecturers need to promote metacognitive awareness in students, so that students are able to develop their thinking strategies well in playing music, especially in guitar classes.